Effects of Spaced and Massed Distribution Instruction on EFL Learners' Recall and Retention of Grammatical Structures - Amir Mashhadi; Mohammad Taghi Farvardin; Aminollah Mozaffari (Teaching English Language, 2017)
The efficacy of massed and spaced distribution instruction in second/foreign language learning is still an issue of debate. Moreover, few studies have probed the possible effect of spaced distribution practice on English as a foreign language (EFL) learners' recall and retention of grammatical structures. This study, therefore, aimed to examine this issue by recruiting 72 Iranian EFL junior high school students in a public school. The participants were randomly assigned to spaced distribution (n = 24), massed distribution (n = 23), and control (n = 25) groups. The massed distribution group had one intensive session on learning the target grammatical structures (i.e., the simple present affirmative, negative, and interrogative forms); the spaced distribution group had three sessions at irregular time intervals; while the control group received no instruction. To collect data on the recall and retention of the target structures, an error correction test was administered to the participants three times as the pretest, immediate posttest and delayed posttest. The results of the repeated measures mixed ANOVAs, one-way ANOVAs, and post hoc Tukey tests revealed that the spaced distribution group significantly outperformed the other two groups on the delayed posttest. However, there was no significant difference between the spaced and massed distribution groups on the immediate posttest. The findings suggest that EFL practitioners can incorporate spacing as an instructional strategy into the curricula and educational materials to foster the recall and retention of English grammatical structures.